A Distributed Self-Reconfiguration Planning Algorithm for Modular Satellites - Tian, Xiaoman; Xiao, Bing (Chinese Control Conference, 2022)
As a new form of space operation, modular satellites system is usually composed of multiple modules with uniform docking interfaces that can be transformed into different configurations by themselves to achieve on-orbit variable missions. The reconfiguration path planning problem is finding what sequence of actions are required for a configuration to transform into another. In this paper, we present a novel self-reconfiguration planning algorithm based on the graph theory to support multi-module motion simultaneously for modular satellites. The method gains homogeneous and reconstruction parts by comparing the initial configuration with goal configuration efficiently. It is not only can reduce the number of participating in reconstruction modules but also improve the efficiency of reconstruction. Then the reconfiguration actions can be executed using Dijkstra algorithm so that each module can efficiently finish its reconfiguration task which results in a global reconfiguration for the system. And The priority motion function to solve local conflict between modules. Finally, reconfiguration examples are provided and results verify the feasibility and superiority of the proposed algorithm.